KETERKAITAN ANTARA FOREIGN DIRECT INVESTMENT, PERDAGANGAN INTERNATIONAL, INDEKS PERSEPSI KORUPSI, NILAI TUKAR DAN PERTUMBUHAN EKONOMI DI INDONESIA - Cut Nurul Iman; Setyo Tri Wahyudi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The growth of Indonesia's GDP per Capita can be said to be quite stable and domestic consumption is still the largest contributor to the Indonesian economy, while Indonesia. Trade openness has the potential to increase economic growth by increasing efficient resource allocation and increasing factor productivity through technology adoption and knowledge transfer. Apart from that, FDI is also one of the keys to increasing efficient resource allocation and increasing factor productivity through technology adoption and knowledge transfer. Currently the value of international trade and FDI is still smaller than the domestic consumption sector. Furthermore, Indonesia's corruption perception index can also be said to be quite high, this could be an indicator of the perception or distrust of the public and investors towards the Indonesian government. An immediate increase in corruption will reduce economic investment, creating a general distortion. Based on the description above, it can be seen that Indonesia has not yet maximized these three factors (capital, human resources, technology) which can be obtained from international trade and FDI and also that Indonesia's corruption index level is still high. The method used is the Vector Error Correction Model. The research results show that the export variable has the highest influence on Indonesia's economic growth.